Introducing point-of-care ultrasound through structured multifaceted ultrasound module in the undergraduate medical curriculum at the University of Hong Kong - Coiffier, Benedicte (Ultrasound, 2019)
Incorporation of point-of-care ultrasound in the undergraduate medical curriculum is of great importance to ensure early exposure and safe use of the modality. We aimed to assess the students' learning experiences following implementing an ultrasound module in the medical curriculum at the University of Hong Kong. Medical students in semester 6 (n = 221) were enrolled in the module in 2018. It consisted of 1 hour of didactic lecture, followed by 3 hours of hands-on session. The students had the opportunity to enroll into a four-week Special Study Module to further practice their skills. The students had access to an e-learning platform to assist in their learning. Outcome measures include task-based performance, quizzes, feedback, and round-table discussion to assess the learning experiences. The module was highly rated by over 90% of students (response rate of 96%). Students practiced on peer subject on upper abdominal scanning. Post-training assessment showed an increment of 16% in their understanding of the modality. Students were motivated to enroll into the Special Study Module, where they were trained and became proficient with Focused Assessment with Sonography with Trauma. More than 86% of the students found the e-learning platform easy to use and assisted the training session. Round-table discussion suggested more simulated clinical cases to be added and expansion of future modules. Ultrasound module was successfully implemented into the undergraduate medical curriculum at the University of Hong Kong through new pedagogical approaches. This integration was highly rated by the medical students with improved awareness and better understanding of point-of-care ultrasound.